IMPLEMENTASI PEMBELAJARAN BERBASIS BUDAYA LOKAL DALAM MENINGKATKAN SIKAP POSITIF DISIPLIN SISWA SEKOLAH DASAR - Johannes, Nathalia Yohanna; Ritiauw, Samuel Patra; Mahananingtyas, Elsinora; Nurhayati, Nurhayati (Program Studi Bimbingan dan Konseling, Universitas Pattimura, 2019)
The aim of conducting this research is to know the implementation of cultural local based learning in enhancing positive attitude of discipline to fourth grade students of SD Negeri 85 Ambon. The result of preliminary observation showed that the students were less of positive attitude. The less of students' less positive attitude can be seen on time discipline, not neatly in wearing uniform,disobey school rules, and undisciploned in attitude. Based on these problems, the research was carried out to increase positive discipline of attitude toward the implementation of cultural local based learning.